Network pharmacology approach to identifying optimal therapeutic targets in cancer drug discovery and development: Bibliometric analysis and scoping review - Rovik, Anwar; Henra, Henra; Rahman, Farras Alifia; Afkarina, Izza; Conara, Flafiani Cios (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2026)
A rise in chronic diseases, including cancer, increasingly strains public health. While conventional drug discovery often focuses on single molecules, this method frequently fails to address complex diseases with multiple causes. Network pharmacology, a systems biology approach, provides a more complete understanding of disease mechanisms by analyzing intricate biological networks. By combining multi-omics data and computational models, network pharmacology helps identify new drug targets and cellular pathways. This approach is especially promising in cancer research, where it can reveal complex interactions between genes, proteins, and metabolites. This review explains the principles of network pharmacology and its use in cancer drug discovery. We cover the process, from network building and analysis to experimental testing. Additionally, we examine how network pharmacology can speed up the development of personalized cancer treatments.